If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2u + 2 = 5p + -10 Reorder the terms: 2 + 2u = 5p + -10 Reorder the terms: 2 + 2u = -10 + 5p Solving 2 + 2u = -10 + 5p Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2u = -10 + -2 + 5p Combine like terms: 2 + -2 = 0 0 + 2u = -10 + -2 + 5p 2u = -10 + -2 + 5p Combine like terms: -10 + -2 = -12 2u = -12 + 5p Divide each side by '2'. u = -6 + 2.5p Simplifying u = -6 + 2.5p
| 1+-2g=5 | | 4/15-3/15 | | 13a-1=90 | | -(6y+3)-(-5-4)=-7 | | P=4c-20+2c | | 73=4p+7 | | 2=4-2y | | F(x)=x*2+6x+15 | | -3(5s-2)-6=-3(9s+2)-5 | | -9=3k+-3 | | 2y^2-12y+8=0 | | 50=65+10t-5t^2 | | 3x^2+78=0 | | .65x+.05(14-x)=.10(-17) | | 5=a/-11 | | .18(24)+.03x=.09(18+x) | | 1/5y+11=3-3/5y | | 4x+7-9=-14 | | 6+2k=8 | | x=2.5(12.5)-26.25 | | 1=x/2-32/2*x^2 | | 5x+3=-8x+16 | | 6x^4-28x^3-10x^2=0 | | (-9x^3+9x^2-2x+4)+(4x^3+2x^2-4x-6)= | | 7x-12=2x*8 | | .375x-.2+10=.3x | | 40x+75y=900 | | 24=3(3n-5) | | x/26.5=8.5/11 | | -(2x-2)+4(x+6)=3x+8+1 | | x/-56 | | x/-3-4 |